2009
DOI: 10.1152/ajpgi.00029.2008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of PBEF/Nampt/visfatin are decreased in patients with liver cirrhosis

Abstract: Liver cirrhosis is a catabolic disease associated with a high incidence of insulin resistance and diabetes mellitus. Pre-B cell colony-enhancing factor/ nicotinamide phosphoribosyltransferase/visfatin has been characterized as a novel adipokine with a potential role in glucose metabolism and nicotinamide dinucleotide (NAD) generation. We studied plasma levels and metabolic relevance of visfatin in 19 patients with cirrhosis and 19 body mass index-, age-, and sex-matched controls. In addition, hepatic mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…Circulating visfatin levels are significantly decreased in liver cirrhosis of different origin-namely, posthepatic, alcohol and biliary cirrhosis, compared with healthy controls, presumably owing to decreased hepatic expression and production (65). The different underlying etiologies of liver cirrhosis had no significant impact on plasma visfatin levels or on hepatic visfatin production.…”
Section: Visfatin and Fibrosis In Chronic Hepatitismentioning
confidence: 89%
See 1 more Smart Citation
“…Circulating visfatin levels are significantly decreased in liver cirrhosis of different origin-namely, posthepatic, alcohol and biliary cirrhosis, compared with healthy controls, presumably owing to decreased hepatic expression and production (65). The different underlying etiologies of liver cirrhosis had no significant impact on plasma visfatin levels or on hepatic visfatin production.…”
Section: Visfatin and Fibrosis In Chronic Hepatitismentioning
confidence: 89%
“…Patients in the early clinical stages of cirrhosis-child class A liver cirrhosisalready had decreased plasma visfatin levels that were, however, significantly higher than those of patients with child class B or C liver cirrhosis. Plasma visfatin in cirrhosis is not associated with IR and plasma glucose but correlates with hepatic glucose production and the arterial ketone body ratio, indicating a potential link between the NAD-generating properties of visfatin and metabolism (65). In patients with NAFLD, there was no difference between individuals with and without fibrosis, but there were no data clarifying whether any of the patients analyzed had cirrhosis (42).…”
Section: Visfatin and Fibrosis In Chronic Hepatitismentioning
confidence: 93%
“…To our knowledge, only 2 studies in Turkey and the United Kingdom have explored the association of circulating adipsin and NAFLD, but they did not find any significant difference of circulating adipsin concentrations among NAFLD and non-NAFLD subjects [15,16]. Visfatin is also an adipokine secreted by various tissues and involves in regulating glucose metabolism, insulin resistance, and inflammatory action [17][18][19]. Chang et al [20] found that circulating visfatin was positively associated with obesity, T2DM, metabolic syndrome (MetS), and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 98%
“…The role visfatin in acute and chronic liver degenerations and fibrosis has not been well studied before and there are some controversial results. While it has been shown that visfatin concentration is lower in cirrhotic patients [55] , in other studies no correlation was found between fibrosis and serum visfatin level [56,57] . We also did not detect any significant changes in serum visfatin level on any of the groups studied indicating that visfatin has no apparent role on the omega-3 supplementation or the liver injury induced by CCl 4 .…”
Section: Discussionmentioning
confidence: 96%